Políticas laborales en España para los inmigrantes latinoamericanos - Sacristán Romero , Francisco (Cuadernos de Trabajo Social, 2006)
Active employment policies for Latin American immigrants seek to contribute to the improvement of possibilities of incorporation and work continuance of these workers who are so tied to the Spanish culture, combining, at the same time, flexibility and security in employment. Moreover, in macroeconomic terms, acting selectively upon supply and demand with measures such as promoting private initiative, aiding mobility to sectors with sufficient demand or directly creating employment, permit imbalances or misalignments in the labor market to be lessened.